Design for e-training - Christian Östlund (Copenhagen Business School (CBS), 2017)
This thesis is about designing technology that supports and enhances learning in and for the workplace. This is realized through an e-training system of web lectures. Designing e-training means designing for interaction in a user friendly way while accommodating for the pedagogical and instructional strategies that are inherent in learning systems. The objective of this thesis is to inform how technology can be designed to support workplace training by acknowledging the context demands of every day work. The context for this thesis is the government authority in Sweden called the county administration. The research in this thesis follows the approach of design science research and design principles for e-training through web lectures emerged in collaboration with members of the county administration through four design cycles of problem awareness: conceptual suggestion, system development, and evaluation. The perspective on learning adopts that of socio-cultural learning since it acknowledges the importance of context by stressing the relationship between learning and the context in which the learning occurs. A framework called authentic e-learning with nine core design principles was chosen as a kernel theory. The first version of the web lecture application was based on the unchanged design principles of authentic e-learning. The design principles were then evaluated in the context of a work place and after four design cycles some of the original design principles was still unaltered, some was adapted to the conditions of work place learning and new principles emerged from the evaluation process. The thesis concludes with eight design principles for e-training through web lectures.
hdl:10398/9478
Keywords: 650